Rapid Convergence of Approximate Solutions for Fractional Differential Equations. (4th May 2020) - Wu, Xiran; Bao, Junyan; Sun, Yufeng
Abstract : In this paper, we develop a generalized quasilinearization technique for a class of Caputo's fractional differential equations when the forcing function is the sum of hyperconvex and hyperconcave functions of order m (m ≥ 0 ), and we obtain the convergence of the sequences of approximate solutions by establishing the convergence of order k (k ≥ 2 ).